2009
DOI: 10.1002/app.31079
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of polypyrrole layers doped with glutamic ions

Abstract: Electrochemically synthesized polypyrrole thin films doped with glutamic ions were investigated as interesting materials for potential use as molecularly selective surfaces. Pyrrole and glutamate interact in aqueous solution, resulting in the formation of a prominent band at 240 nm in the absorption spectra of the solution. This feature was assigned to the formation of a complex, which significantly influences the electrochemical deposition of polypyrrole films doped with glutamate. It was also detected that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In investigations of the mechanism of the potentiostatic deposition of MIPPy films in the presence of glutamate, the electropolymerization conditions, including concentrations and the concentration ratio of the template and functional monomer as well as the solution pH, were optimized [ 100 ]. It appeared that the mechanism was unique, being different from that of the analogous mechanism of deposition of the film of MIPPy templated with glutamate in an alkaline solution (pH = 9.0).…”
Section: Electrosynthesized Polymers In Molecular Imprintingmentioning
confidence: 99%
“…In investigations of the mechanism of the potentiostatic deposition of MIPPy films in the presence of glutamate, the electropolymerization conditions, including concentrations and the concentration ratio of the template and functional monomer as well as the solution pH, were optimized [ 100 ]. It appeared that the mechanism was unique, being different from that of the analogous mechanism of deposition of the film of MIPPy templated with glutamate in an alkaline solution (pH = 9.0).…”
Section: Electrosynthesized Polymers In Molecular Imprintingmentioning
confidence: 99%
“…This assumption is supported by previous reports of polymerization of pyrrole in the presence of simple amino acids. Specifically, the finding of strong interaction between glutamic ions and pyrrole moieties during the electrochemical deposition of PPy films and the glycine inclusion in PPy matrix when the polymer was prepared by chemical oxidation of pyrrole with APS in the presence of this amino acid …”
Section: Resultsmentioning
confidence: 99%
“…Meteleva‐Fischer et al . investigated the mechanism of the electrochemical deposition of PPy films doped with l ‐glutamic ions . Their study showed that glutamic ions interact strongly with pyrrole molecules, apparently in form of a complex.…”
Section: Introductionmentioning
confidence: 99%
“…11 For instance, a poly(o-phenylenediamine) lm was used for the detection of glucose 12 and polypyrrole-based MIPs enabled the detection of glutamic acid as a template molecule. 13 An amperometric morphine sensor 14 was also prepared using the concept of MIPs. Besides, the detection of analytes binding with electropolymerized layers of MIPs was performed using different techniques.…”
Section: Introductionmentioning
confidence: 99%